신재생에너지의 에너지 하베스팅을 위한 DPP시스템의 구성과 효율계산 - 박승화(Seung-Hwa Park); 이현재(Hyun-Jae Lee); 손진근(Jin-Geun Shon) (전기학회 논문지 P권, 67(3), 2018)
Energy harvesting technology is drawing attention as a means of collecting various eco-friendly energy and accumulating residual energy. Recently, differential power processing (DPP) is being developed as part of energy harvesting. This is being studied as a solution to the loss of power generation between power modules and the problems caused by module small losses depending on the size of power production. In this paper, we propose the necessity of the DPP by comparing and analyzing energy harvesting related module integration system and power supply efficiency of DPP. The power efficiency of the converter and the power difference between the wind power and the photovoltaic power supply have been changed to demonstrate the effectiveness of the proposed system.